Structural deformation monitored by vibrational properties and orbital modeling in (Pb,Sm)TiO3 systems - Paris, E. C. [UNESP]; Gurgel, M. F. C.; Joya, M. R.; Casali, G. P.; Paiva-Santos, C. O. [UNESP]; Boschi, T. M.; Pizani, P. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Pb1-xSmxTiO3 (PST) powders with x varying from 0 to 0.1 were obtained by the polymeric precursor method, a soft chemical route. The vibrational properties relating tetragonal to pseudo-cubic phase transition were studied by Raman spectroscopy. The results obtained showed that the phase transition is extremely dependent upon the samarium content and presents a diffuse behavior. Monitoring of the oxygen 2p and titanium 3d orbitals was performed by the periodic mechanical quantum method, revealing the changes that occur with the distribution and contribution of the hybrid orbitals due to the samarium influence. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Oxides; Chemical synthesis; Ab initio calculations; luminescence